Clinical events and patient-reported outcome measures during CKD progression: findings from the Chronic Renal Insufficiency Cohort Study. Issue 9 (16th December 2020) - Grams, Morgan E; Surapaneni, Aditya; Appel, Lawrence J; Lash, James P; Hsu, Jesse; Diamantidis, Clarissa J; Rosas, Sylvia E; Fink, Jeffrey C; Scialla, Julia J; Sondheimer, James; Hsu, Chi-Yuan; Cheung, Alfred K; et al.
Abstract: Background: Patients with chronic kidney disease (CKD) face risks of not only end-stage kidney disease (ESKD), cardiovascular disease (CVD) and death, but also decline in kidney function, quality of life (QOL) and mental and physical well-being. This study describes the multidimensional trajectories of CKD using clinical events, kidney function and patient-reported outcome measures (PROMs). We hypothesized that more advanced CKD stages would associate with more rapid decline in each outcome. Methods: Among 3939 participants enrolled in the Chronic Renal Insufficiency Cohort (CRIC) Study, we evaluated multidimensional disease trajectories by G- and A-stages of enrollment estimated glomerular filtration rate (eGFR) and albuminuria, respectively. These trajectories included clinical events (ESKD, CVD, heart failure and death), eGFR decline and PROMs [kidney disease QOL (KDQOL) burden, effects and symptoms questionnaires, as well as the 12-item short form mental and physical component summaries]. We also evaluated a group-based multitrajectory model to group participants on the basis of longitudinal PROMs and compared group assignments by enrollment G- and A-stage. Results: The mean participant age was 58 years, 45% were women, mean baseline eGFR was 44 mL/min/1.73 m 2 and median urine albumin:creatinine ratio was 52 mg/g. The incidence of all clinical events was greater and eGFR decline was faster with more advanced G- and A-stages. While baseline KDQOL and physical component measures were lower with more advanced G- and A-stage of CKD, changes in PROMs were inconsistently related to the baseline CKD stage. Groups formed on PROM trajectories were fairly distinct from existing CKD staging (observed agreement 60.6%) and were associated with the risk of ESKD, CVD, heart failure and death. Conclusions: More advanced baseline CKD stage was associated with a higher risk of clinical events and faster eGFR decline, and was only weakly related to changes in patient-reported metrics over time. GRAPHICAL ABSTRACT: